PENGARUH ATRIBUT PRODUK DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA JUPITER SERIES PADA DEALER YAMAHA AGUNG MOTOR SEMARANG - Setiawan Setiawan; Agus Hermani; Sri Suryoko (Universitas Diponegoro, 2012)
Product Attributes and Advertisement are the factors that influence Purchasing Decisions. An attribute of the product is advantage offered the product motorcycle Yamaha Jupiter Series characteristic Attribute Products that are superior and are characteristic of these products than the product of another. Attribute this product then informed to consumers largely through advertising. By the presence of an attribute the product which is good and activities of advertising done continuous it is hoped to create high level of the decision of the purchase. Creation of Product Attributes and a good Advertisement will have an impact on sales, because consumers assume better buy Yamaha Jupiter Series on dealer Yamaha Agung Motor Semarang because it has more value than any other. This research would like to solve many problems, that is how much the Product Attributes influencing to the Purchasing decision, how much the advertisement influence to the purchasing Decisions, and how much the Product Attributes and Advertisement influencing to the consumer Purchasing Decisions. This research is an explanatory research. The data collected by questionnaire to 94 respondens of Yamaha Agung Motor Semarang dealer’s customers. The data analized used validity test, reliability test, simple linier regretion, multiple linier regretion, determination coefficient, t-test and F test. From the result by SPSS analisis can be include that : there is a positive and significant influences between the Product Attributes to the Purchasing Decisions, There is a positive and significant influences between the Advertisement to the Purchasing Decisions. There is a positive and significant influences between the Product Attribute and Advertisement to the Purchasing Decision. Product Attributes (X1) and Advertisement (X2) contributed for 67,9% for the Purchasing Decisions and 32,1% influenced by the others factors. Company need to improve Product Attributes and Advertisement to face competition that continues to increase.